Effects of added fluted pumpkin seed flour on the chemical composition, physical and sensory quality of acha-wheat bread - Ayo, Jerome Adekunle; Tailem, Paul; Osabo, Peace; Kave, Sughen (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2024)
This study investigated the effect of incorporating fluted pumpkin seed flour (FPSF) into acha-wheat bread on its chemical composition, physical attributes, and sensory qualities. Acha-wheat bread samples were prepared by substituting wheat flour with varying percentages (5%, 10%, 15%and 20%) of FPSF. Proximate analysis revealed that the addition of FPSF significantly increased the protein and dietary fiber content of the bread from 10.79- 13.03 and 0.04-0.21%, while ash and fat content also showed slight increment from 1.40-2.50 and 5.47-6.71% respectively. The moisture content decreased marginally with increasing FPSF concentration. The physical characteristics: loaf volume decreased with higher FPSF levels which could be attributed to reduced gluten content and impaired gas retention. However, crust and crumb color improved, yielding a golden colour and appealing appearance. Generally, sensory evaluation showed that bread with up to 10% FPSF substitution was the most preferred in terms of taste, texture, and overall quality. Incorporating FPSF in acha-wheat bread enhances its nutritional profile and certain physical qualities up to a certain level, it may necessitate adjustments in formulation to optimize sensory attributes and maintain consumer acceptability.